Fejezetek a játékpedagógia történetéből - Bús, Imre (Kultúratudományi Szemle, 2023)
The game has been a part of education for a long time but could not become a commonly used tool. Today, it does not have a decisive role in public education either, even though the literature offers adequate sources and motivation for the pedagogical usage of gamification. The study presents some significant pedagogical researches that represent the progression in the history of pedagogy. With their help, it is possible to plan modern pedagogical processes adapted to the conditions of our world.